Primary AL Amyloidosis Presenting with Macroglossia and Spontaneous Chest Wall Ecchymosis in a Young Male - Masud, Aamina; Abid, Seemab; Afique, Muhammad (Journal of Rawalpindi Medical College, 2026)
We report the case of a 35-year-old male who presented with progressive macroglossia associated with dysarthria and worsening dyspnea with no accompanying stridor, dysphagia, or features suggestive of acromegaly; however, the patient specifically reported difficulty pronouncing words starting with the letter “R.” Clinical examination revealed evidence of both cardiac and pulmonary involvement. Comprehensive investigations were conducted to rule out alternative causes of macroglossia. An abdominal fat pad biopsy demonstrated Congo red positivity with apple-green birefringence under polarized light, confirming the diagnosis of primary AL amyloidosis.⁴ The patient was initiated on chemotherapy, stabilized, and subsequently referred to the oncology department for outpatient follow-up. Keywords: Immunoglobulin Light-chain Amyloidosis, Macroglossia, Ecchymosis